The Textbook analysis on students' book of Symphony 1 English course book for Senior High School Grade X viewed from higher order thinking skills - Sari, Riski Norita; Sakhiyya, Zulfa (ELT Forum: Journal of English Language Teaching, 2020)
This study analyzes an English Course textbook entitled Symphony to find out to what extent higher and lower order level thinking is used in the reading tasks. The questions central in this study are: how the composition and to what extent are reading tasks on the Symphony 1 Course Book for Senior High School contribute to build students' Higher Order Thinking Skill? This descriptive qualitative research also adopted the cognitive process of Revised Blooms' Taxonomy as the instrument. Cognitive levels used for this research were remembering, understanding, applying, analysing, evaluating and creating. Then, the researcher calculated the percentage and frequencies the cognitive level appearances from the total questions analysed. Then questions indicated of HOTS were analysed again by using instruments from Keshta and Sheif (2013) to know the variety of questions found in the textbook. The results showed that Lower Order Thinking Skills (LOTS) dominate the reading tasks of the textbook. It shows LOTS were found 63% while HOTS 37%. It can be concluded that HOTS dominate the textbook which discourages students to think critically. Based on the findings, it is recommended that textbook writers need to advance HOTS in order to develop students' critical thinking skills.